Surface characterization and antibacterial response of silver nanowire arrays supported on laser-treated polyethylene naphthalate - Polívková, M; Štrublová, V; Hubáček, T; Rimpelová, S; Švorčík, V; Siegel, J (Materials science & engineering. C, Materials for biological applications, 2017)
Polymeric biomaterials with antibacterial effects are requisite materials in the fight against hospital-acquired infections. An effective way for constructing a second generation of antibacterials is to exploit the synergic effect of (i) patterning of polymeric materials by a laser, and (ii) deposition of noble metals in their nanostructured forms. With this approach, we prepared highly-ordered periodic structures (ripples) on polyethylene naphthalate (PEN). Subsequent deposition of Ag under the glancing angle of 70° resulted in the formation of self-organized, fully separated Ag nanowire (Ag NW) arrays homogenously distributed on PEN surface. Surface properties of these samples were characterized by AFM and XPS. Vacuum evaporation of Ag at the glancing angle geometry of 70° caused that Ag NWs were formed predominantly from one side of the ripples, near to the top of the ridges. The release of Ag+ ions into physiological solution was studied by ICP-MS. The results of antibacterial tests predetermine these novel structures as promising materials able to fight against a broad spectrum of microorganisms, however, their observed cytotoxicity warns about their applications in the contact with living tissues.
Keywords: lasery; povrchové vlastnosti; polyethylen; Silver; Lasers; Vacuum evaporation; Staphylococcus epidermidis; Photoelectron Spectroscopy; antibakteriální látky; Nanowires; Polyethylene naphthalate; Surface properties; Escherichia coli; Microscopy, Atomic Force; Polyethylene; Laser patterning; mikroskopie atomárních sil; nanodráty; fotoelektronová spektroskopie; Anti-Bacterial Agents; Antibacterial effects; Surface Properties; stříbro